Morphology of juvenile phase of Achelous spinimanus (Latreille, 1819) (Crustacea, Decapoda, Portunidae) reared in laboratory - Bolla Junior, Eduardo Antonio [UNESP]; Negreiros Fransozo, Maria Lucia [UNESP] (Cambridge Univ Press, 2016)
The swimming crab Achelous spinimanus is an important fishery component of several countries in the Western Atlantic; therefore, knowledge of the different phases of its life cycle is essential for good management of this resource. The juvenile development of A. spinimanus was investigated in the laboratory, from megalopae captured in neuston samples at Ubatuba, Sao Paulo, Brazil (23 degrees 26'S 46 degrees 09'W), during the summer months of 2005-2007. Rearing was performed in a constant temperature (25 +/- 1 degrees C), filtered seawater from the collection location (35 psu) and natural photoperiod. We obtained nine stages of the juvenile phase. All the morphological characters that allow the recognition of the first juvenile stage were drawn and described, as well as the main alterations that occur in the following stages. The sexual differentiation based on the number of pleopods becomes apparent from the third stage on. Some important characters in the identification of the species at the juvenile phase are the number of segments on the exopod of antennule, on the antennal flagellum and on the palp of mandible, beyond the absence of pleopods (even rudimentary) in the first stage.
Keywords: Swimming crab; Brachyura; development; post-larval; immature